2015
DOI: 10.1016/j.ejor.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Integrating soft and hard operational research to improve surgical centre management at a university hospital

Abstract: a b s t r a c tThe aim of this work is to present the practical applications of an integrated use of soft and hard methodologies applied in a case study of the Surgical Centre of the University Hospital Clementino Fraga Filho, where the low volume of surgeries is of major concern. The proposed approach is particularly appropriate in situations where there is limited time, financial resources, and institutional cooperation. Cognitive maps were used to elicit the perspectives of health professionals, which suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Some use of these have been incorporated in SimLean Facilitate, but Robinson et al (2014) also call for two other developments towards fully-facilitated DES: i) a mindset change to consider simpler (and rapidly-built) models to facilitate understanding and discussion rather than aiming for predictive accuracy as a default, and ii) a technical solution involving a software environment that enables a facilitator/modeller to capture the conceptual model and perform model coding live with stakeholders. Including model coding in facilitated sessions is also noted as a future challenge by Pessôa, Lins, da Silva, and Fiszman (2015).…”
Section: Facilitation In Des In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Some use of these have been incorporated in SimLean Facilitate, but Robinson et al (2014) also call for two other developments towards fully-facilitated DES: i) a mindset change to consider simpler (and rapidly-built) models to facilitate understanding and discussion rather than aiming for predictive accuracy as a default, and ii) a technical solution involving a software environment that enables a facilitator/modeller to capture the conceptual model and perform model coding live with stakeholders. Including model coding in facilitated sessions is also noted as a future challenge by Pessôa, Lins, da Silva, and Fiszman (2015).…”
Section: Facilitation In Des In Healthcarementioning
confidence: 99%
“…Case B demonstrated that BPMN can be a useful tool for process mapping, even if DES does not follow. It is starting to be used by analysts and practitioners to map healthcare processes with stakeholders (Bochicchio, Bruno, & Longo, 2011;Vandborg et al, 2012); and Pessôa et al (2015) use the BPMN palette in Bizagi as a tool for drawing their DES activity cycle diagram for a project on surgical flows (though they do not follow the conventions of BPMN and it appears that the model presented would not run as intended if translated into BPSim.) One of the ambitions of improvement staff at Salford Royal was to widen and standardise the documentation of patient pathways.…”
Section: To What Extent Can Bpmn Support Facilitated-mode Model Coding?mentioning
confidence: 99%
“…They concluded that soft TQM elements have major effects on customer satisfaction and fi nancial performance. Generally, in service provider fi rms the combination of soft and hard methodologies can provide managers with quantitative fi gures that measure the outcome of the adopted and committed practices by the employees (Pessôa et al, 2015). In this respect, Rahman and Bullock (2005) have discovered a signifi cant relationship between soft and hard TQM practices, which affects positively the company's performance.…”
Section: Tqm Practices and Performancementioning
confidence: 99%
“…The second is the k-means algorithm, a cluster analysis technique that is based on centroids to calculate the pertinence of points to groups. The formal quantitative modeling was preceded by a problem structuring qualitative method that used cognitive mapping, integrated in the multimethodology (Pessoa et al 2015), however outside the scope of the present paper. After clustering smartphones and determining smartphone profiles, we perform smartphone assessment through DEA modeling in each cluster, thus ensuring to evaluate similar profiles, avoiding, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…However, technological homogeneity is one important assumption in DEA, since it allows direct comparison between operational units. By complying with this concept, we propose a multimethodology approach (Pessoa et al 2015) that first applies cluster analysis to search for homogeneous clusters of smartphones, which still stand for consumer preference profiles. After that, we use data envelopment analysis (DEA) to assess the performance of units inside each cluster, thus providing smartphones assessment model that analyzes different alternatives of smartphones, appropriate to specific profiles to support smartphone consumers in decision-making.…”
mentioning
confidence: 99%